KARAKTERISASI KONDISI OPTIMUM - Aline Puspita Kusumadjaja, ; Juli Astri, (Matematika dan Sains, 2010)
A study to investigate the optimum condition of bromelein enzyme has been carried out. The condition investigated were pH and temperature, based on measurement of enzyme activity which is defined as mmol tyrosin that are released in reaction between bromelein enzyme and casein as substrat per minute. In this research, the bromelein enzyme was isolated from nanas with Cayenne variety, and was partially purified by precipitation method using ammonium sulfat. The work result showed that the optimum condition of bromelein enzyme are in pH 7 with activity 1,368 U/mL, at 55oC with activity 1,282 U/mL.mmol tyrosin that are released in reaction between bromelein enzyme and casein as substrat per minute. In this research, the bromelein enzyme was isolated from nanas with Cayenne variety, and was partially purified by precipitation method using ammonium sulfat. The work result showed that the optimum condition of bromelein enzyme are in pH 7 with activity 1,368 U/mL, at 55oC with activity 1,282 U/mL.